Rethinking the policing of homelessness: navigating the urban ‘game’ as social peacekeepers - Kyprianides, Arabella (Policing and society, 2024)
This paper considers interactions between police and individuals experiencing homelessness, a fundamental aspect of contemporary urban dynamics. The challenges and vulnerabilities faced by the ‘street population’ intersect with policing priorities in ways that prompt re-evaluation of conventional policing methods. Beginning with an exploration of existing research, Section 1 analyses police interactions with the street population, illuminating the complexities, challenges, and outcomes of these encounters. Section 2 takes an ethics-based approach to scrutinise the implicit assumptions and values underpinning traditional policing. By dissecting the moral implications of these encounters, the paper underscores the necessity for an alternative framework grounded in compassion, empathy, and social welfare. Section 3 considers the potential for a paradigm shift in policing methods concerning the street population towards community-based strategies, restorative justice practices, and collaborative partnerships between police and social service providers. By combining research findings, ethical considerations, and potential strategies, the paper contributes to a deeper understanding of these interactions, ultimately seeking to enhance the well-being of people experiencing homelessness and promote community harmony. By challenging existing paradigms and advocating for a more empathetic and socially conscious approach, the paper strives to ignite meaningful transformations that address the complex dynamics between police and the street population.